Identification of the Condition the Sugarcane Supply Chain at the Wringin Anom Sugar Factory, Situbondo Regency - Andina Mayangsari (Future Science)
The agricultural sector plays an important role in the economy in Indonesia, one of which is the plantation sub-sector. Sugarcane is one of the many plantation crops that have high economic value and are the main ingredient of the sugar industry. Sugar is one of the nine staples that are often used by people in their daily lives, and is an important element when driving the national economy. The Wringin Anom Sugar Factory itself is part of the PTPN XI Surabaya work unit which produces sugar. The decline in sugar production has an impact on the decline in the contribution of the sugar industry in Indonesia in achieving sugar self-sufficiency. Improving and enhancing sustainable supply chain management in the sugar industry is expected to increase production yields and be able to maximize added value. This study aims to determine the condition of the sugarcane supply chain at the Wringin Anom Sugar Factory, Situbondo. The method used in this research is descriptive analytical. The research location is the Wringin Anom Sugar Factory in Situbondo Regency. The results show that the sugarcane supply chain structure at the Wringin Anom Sugar Factory has less than optimal performance.